PERANCANGAN KAWASAN WISATA KONSERVASI PENYU DI TANJUNG KELUANG PANGKALAN BUN DENAGN PENDEKATAN ARSITEKTUR EKOLOGIS - Faizah , Auliani Noor; Mardika, I Kadek; Ngini, Giris (Jurusan Arsitektur UPR, 2024)
West Kotawaringin Regency, with the capital city of Pangkalan Bun, has great potential to be developed into a leading tourism destination in Central Kalimantan Province. Many foreign and domestic tourists have come and there are many tourist destinations on offer in West Kotawaringin. One of the destinations is the Tanjung Keluang Nature Tourism Park in Kubu Village, Kumai District. Tanjung Keluang TWA is a peninsula that directly faces the Java Sea, has a beautiful natural landscape and is a place where rare turtles such as hawksbill turtles and green turtles lay their eggs. However, there is still little interest from tourists in visiting there because it has not been managed well, such as very minimal supporting facilities. With the special features that TWA Tanjung Keluang has, it has the potential to be developed as a Turtle Conservation Tourism Area which can support conservation, education and recreation activities. However, by providing supporting facilities in this area, you must pay attention to the planning and design so as not to damage the environment and ecosystem there. Therefore, the design of the Turtle Conservation Tourism Area in Tanjung Keluang will be accommodated with an ecological architecture approach.Choosing an ecological architecture approach is able to minimize estimates of environmental damage that will occur as a result of a development, because it is able to create design results that can maintain natural resources, manage the local climate, create buildings that can reduce environmental pollution, use technology with the aim of saving energy and use natural materials. In this way, there will be harmony between buildings, people, species and the environment in the tourist area.